In vitro modeling of feline gut fermentation: a comprehensive analysis of fecal microbiota and metabolic activity - Ren, Qianle; Li, Yuling; Duan, Mingmei; Li, Jinjun; Shi, Fangshu; Zhou, Yun; Hu, Wanjing; Mao, Junfu; Li, Xiaoqiong (Frontiers in Microbiology, 2025)
The gut microbiota (GM) is a large and diverse microbial community that plays essential roles in host health. The in vitro fermentation model of the fecal GM serves as a valuable complement to food and health research in both humans and animals. Despite advancements in standardized protocols for culturing human GM, research concerning animals—particularly companion animals—remains limited. This study aims to identify the optimal in vitro fermentation method for cat gut microbiota by comprehensively analyzing fecal microbiota and fermentation characteristics. We evaluated seven culture media previously used to simulate the gut microenvironment in humans, dogs, and cats: anaerobic medium base (AMB), Minimum medium (MM), Pet medium (PM), VI medium (VI), VL medium (VL), Yeast culture medium (JM), and yeast casitone fatty acid agar medium (YCFA). Fresh fecal samples were fermented in these media for 48 h, followed by 16S rRNA sequencing to assess bacterial community composition and targeted metabolite monitoring during fermentation. The results revealed that the substrate composition in the medium differentially impacts bacterial community structure and fermentation characteristics. High levels of carbon and nitrogen sources can substantially increase gas production, particularly CO2, while also significantly enhancing the production of short-chain fatty acids (SCFAs). Additionally, substrates with a high carbon-to-nitrogen ratio promote the production of more SCFAs and biogenic amines, and enrich the Bacteroidaceae family, even when the total substrate amount is lower. Comprehensive analysis of gut microbiota and metabolites reveals that PM medium effectively simulates a nutrient-deficient microenvironment in the cat gut during in vitro fermentation. This simulation maintains bacterial community stability and results in lower metabolite levels. Therefore, using PM medium to culture cat gut microbiota for 48 h, without focusing on specific bacterial genera, represents the most suitable in vitro model. This finding contributes to understanding the optimal conditions for simulate cat gut microbiota and may provide a new approach for investigating the food pharmaceuticals on the cat gut microbiota and related health.